Health status and socio-economic factors associated with health facility utilization in rural and urban areas in Zambia - Zyaambo Cosmas; Siziya Seter; Fylkesnes Knut (BMC, 2012)
Abstracts Background With regards to equity, the objective for health care systems is "equal access for equal needs". We examined associations of predisposing, enabling and need factors with health facility utilization in areas with high HIV prevalence and few people being aware of their HIV status. Methods The data is from a population-based survey among adults aged 15years or older conducted in 2003. The current study is based on a subset of this data of adults 15-49 years with a valid HIV test result. A modified Health behaviour model guided our analytical approach. We report unadjusted and adjusted odds ratios and their 95% confidence intervals from logistic regression analyses. Results Totals of 1042 males and 1547 females in urban areas, and 822 males and 1055 females in rural areas were included in the study. Overall, 53.1% of urban and 56.8% of rural respondents utilized health facilities past 12 months. In urban areas, significantly more females than males utilized health facilities (OR=1.4 (95% CI [1.1, 1.6]). Higher educational attainment (10+ years of schooling) was associated with utilization of health facilities in both urban (OR=1.7, 95% CI [1.3, 2.1]) and rural (OR=1.4, 95% CI [1.0, 2.0]) areas compared to respondents who attained up to 7 years of schooling. Respondents who self-rated their health status as very poor/ poor/fair were twice more likely to utilize health facilities compared to those who rated their health as good/excellent. Respondents who reported illnesses were about three times more likely to utilize health facilities compared to those who did not report the illnesses. In urban areas, respondents who had mental distress were 1.7 times more likely to utilize health facilities compare to those who had no mental distress. Compared to respondents who were HIV negative, respondents who were HIV positive were 1.3 times more likely to utilize health facilities. Conclusion The health care needs were the factors most strongly associated with health care seeking. After accounting for need differentials, health care seeking differed modestly by urban and rural residence, was somewhat skewed towards women, and increased substantially with socioeconomic position.